The EU's Controversial Digital Single Market Directive: Should copyright enforcement have precedence over the interests of users in information privacy and fundamental freedoms? - Samuelson, Pamela (Communications of the ACM, 2018)
The article discusses the proposal for a European Union (EU) Digital Single Market (DSM) Directive for copyright law. Topics include the right of researchers to engage in text- and data-mining, possible changes to the responsibilities of internet service providers (ISPs) in the EU, and liability implications of the EU law Article 13.